From assessing language endangerment or vitality to creating and evaluating language revitalization programmes - Obiero, Ogone J. (Nordic Journal of African Studies, 2010)
For over two decades now, linguists, educators and anthropologists have directed their efforts at researching about factors that occasion and result from language shift (Trudgill, 1991; Fishman 1991, 2001, Crystal, 2000; Edwards, 1992; Sasse, 1992; Landweer, 2000; Crawford, 1995; Blair and Freeden, 1995; Dorian, 1981, 1989; Brenzinger et. al. 2003; Paulston, 1994; and Lewis, 2006). However, since the formulation of the Graded Intergenerational Disruption Scale (GIDS) by Fishman (1991) to guide the assessment of language endangerment or vitality, numerous subsequent conceptual models have tended to focus more on evaluating world languages with respect to their shift rather than their revitalization. Drawing from a chronological overview of some metrics that have been proposed by various researchers together with institutions to guide the evaluation of language vitality or endangerment, and with due regard to some attempts at evaluating language revitalization efforts, this paper seeks to highlight key postulates that could inform efforts at building guidelines with which language revitalization activities may be set-up or examined.
Keywords: Language vitality indicators; language shift; language revitalization